Posterior Approach for Sacrococcygeal Posterior Meningocele with Anterior Large Mature Cystic Teratoma - Kaplan, M.; Akgun, B.; Kazez, A.; Ucler, N.; Cobanoglu, B. (Georg Thieme Verlag Kg, 2010)
[Abstract Not Available]